Dynamics from diffraction - Goodwin, A; Tucker, MG; Cope, E; Dove, M; Keen, D (2006)
We explore the possibility that detailed dynamical information might be extracted from powder diffraction data. Our focus is a recently reported technique that employs statistical analysis of atomistic configurations to calculate dynamical properties from neutron total scattering data. We show that it is possible to access the phonon dispersion of low-frequency modes using such an approach, without constraining the results in terms of some pre-defined dynamical model. The high-frequency regions of the phonon spectrum are found to be less well preserved in the diffraction data. © 2006.